COLLABORATION OF LOCAL GOVERNMENT AND STAKEHOLDERS IN THE PREVENTION AND CONTROL OF CHILD MARRIAGE - Indra Kertati; Karningsih Karningsih; Tri Marhaeni Pudji Astuti (Sosiohumaniora, 2023)
Child marriage has become a growing issue in the last 20 years. Even the United Nations 10 years ago warned Indonesia of an emergency for child marriage. As is well known, the Ministry of PA released the number of child marriages in 2000 as many as 63,382 cases, decreased in 2021 to 61,459 cases, and in 2022 decreased drastically to 50,673 cases. The decline in child marriage or Marriage with dispensation is due to better socialization of changes to Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage and several efforts made by the government and regional governments. The decline occurred in several regions in Indonesia, as was the case in Central Java Province. The problem of child marriage is quite complex because it is not only an internal family problem but includes a complicated social security issue and requires collaboration to solve it. Collaboration between the government and stakeholders has been initiated but has not yet been strengthened, so it is necessary to find a way to overcome child marriage. This research was conducted using the mixed method, namely exploring children who were already married to find out conditions before and after Marriage and children’s responses to child marriage. The purpose of this research is to analyze the roles of the government and stakeholders in the prevention and management of child marriage. This research is expected to address how the government and stakeholders collaborate in preventing and dealing with child marriage. This study focuses on patterns of child marriage, children’s responses to child marriage, the role of government and stakeholders, and models of collaboration between local government and stakeholders in preventing and controlling child marriage with the locus of Central Java Province.